The Effect of Bank Health Level and GCG Self Assessment on Banking Performance - Alamsyah, Sustari; AR, Khorida; Susilawati, Desi (Dinasti International Journal of Economics, Finance & Accounting, 2023)
Bank Bukopin's liquidity difficulties in 2020 were triggered by internal problems which resulted in disruptions to payment traffic, money withdrawals and financing distribution, this had an impact on decreasing public trust and causing harm to the banking world. The research aims to prove the effect of banking soundness level and GCG Self-Assessment on the financial performance of Indonesian banks. The research design is quantitative associatif and the unit of analysis is the company's annual report. Samples were taken from a population of banking entities listed on the IDX for the 2017-2021 period through a purposive-sampling technique and data analysis using panel data regression with the E-Views 10 program. The research results prove that simultaneously financial performance (ROA) is influenced by CAR, BOPO, NPL, LDR and SA-GCG. Partially the CAR, BOPO, and NPL variables affect financial performance (ROA). while LDR and SA-GCG do not affect financial performance (ROA). The research findings indicate that the LDR owned by banks is still in a safe condition and the Self-Assessment-GCG made by the bank does not provide a guarantee that it will increase banking performance.